Green product preferences considering cultural influences: a comparison study between Malaysia and Indonesia. Issue 5 (28th May 2021) - Ghazali, Ihwan; Abdul-Rashid, Salwa Hanim; Md Dawal, Siti Zawiah; Aoyama, Hideki; Sakundarini, Novita; Ho, Fu Haw; Herawan, Safarudin Gazali
Abstract : Purpose: There is an increasing awareness among manufacturers to make production more sustainable in Southeast Asian countries such as Malaysia and Indonesia. Manufacturers are now urged to not only focus on the business profit but also concern on environment protection by producing green products. However, issues may arise regarding the preferences of customers on green products, which will vary due to the influence of cultural values. This will give an impact on the marketing of green products. The aim of this study is to identify the influence of cultural values on the green products design in Malaysia and Indonesia. Design/methodology/approach: A pretest on the survey instruments was performed to ensure the reliability and validity of the questionnaire. The collected data were statistically analyzed based on the satisfaction level, confirmatory factor analysis and structural equation modeling. Findings: The results showed that customer preferences in Malaysia were mostly influenced by uncertainty avoidance, long-term orientation and power distance, excluding collectivism and masculinity. In Indonesia, the dimension of uncertainty avoidance and long-term orientation had significant influence, whereas power distance, masculinity and collectivism dimension had no influence. Eco-label was identified as the most important factor for green products in Malaysia and having product services characteristics factor for product lifetime extension in Indonesia. Practical implications: For practices, the cultural values and preferred characteristics identified in this study provide valuable information to policymakers and businesses on what draws customers toward green products in Malaysia and Indonesia. This finding can be used as supported data for the policymakers in order to achieve sustainable development goal (SDGs) in Malaysia and Indonesia. Originality/value: The findings of this study provide valuable information for designers to design products with green characteristics that cater to the consumer market in Malaysia and Indonesia, as well as other countries which may have similar cultural traits.